Disentangling the Role of Contract Types and Sector Disparities for Public Service Motivation - Grund, Christian; Thommes, Kirsten
The intention of "doing good for society" is regarded to be a crucial motivator for employees in the public sector in order for them to perform well. Recent research in the public sector literature calls for a deeper understanding of how this specific public service motivation (PSM) is shaped. In our paper, we analyze how different degrees of inclusion in the public sector impact PSM. We also investigate how prospects of employment relations (fixed-term versus permanent contracts), temporal differences (part-time versus full-time employment), and actual jobs (core versus subsidiary jobs) moderate PSM in public service. Our findings show that aspects of PSM are affected by these employment characteristics in various ways, suggesting that the factors influencing PSM are multifaceted and that actual employment conditions have to be taken into consideration when assessing PSM.

Cooperation in Diverse Teams: The Role of Temporary Group Membership - Grund, Christian; Harbring, Christine; Thommes, Kirsten
In organizations, some team members are assigned to a team for a predefined short period of time, e.g., as they have a temporary contract, while others are permanent members of the same team. In a laboratory experiment we analyze the cooperation levels resulting from diverse teams, where some team members remain with a team and others are switching teams. Our results reveal that teams consisting partly of members with temporary membership display a lower productivity compared to teams of permanent team members only. First, temporary team members cooperate less than permanent team members. Second, individual effort decisions increase with the number of team mates who are of the same type. This second effect holds for both temps and permanents. We argue that social identity is affected by team composition and the individuals' role in a team.

Künstliche Intelligenz in der industriellen Arbeitswelt - Papenkordt, Jörg; Gabriel, Stefan; Thommes, Kirsten; Dumitrescu, Roman
Im Rahmen dieser Studie wird der Status Quo des KI-Einsatzes in der industriellen Arbeitswelt in der Region OstWestfalenLippe erfasst und beschrieben. Dadurch wird eine Grundlage geschaffen, um eine zielführende Unterstützung der Gestaltung von durch Künstliche Intelligenz (KI) gestützter Arbeitsprozesse in Unternehmen zu ermöglichen, indem beispielsweise bedarfsbezogene Maßnahmen entwickelt und durchgeführt sowie weiterer Forschungsbedarf aufgezeigt wird. Die Befragung wurde im Jahr 2021 von dem Kompetenzzentrum Arbeitswelt.Plus sowie dem Spitzencluster it’s OWL initiiert. Dabei sind drei Zielgruppen – Unternehmensleitung, Personalabteilung (HR) sowie Arbeitnehmer*innen – adressiert worden. Insgesamt nahmen 317 Personen aus 89 verschiedenen Unternehmen bzw. Organisationen an der Befragung teil – zu 38 % Unternehmer*innen, zu 13 % Personaler*innen und zu 49 % Arbeitnehmer*innen. Die meisten der Teilnehmenden stammten aus der Elektroindustrie, dem Maschinenbau sowie dem Informations- und Kommunikationstechnologie (IKT)-Sektor. Die Befragungsergebnisse zeigen, dass sich die meisten Unternehmen in der Anfangsphase der KI-Nutzung befinden. Zwischen einzelnen Unternehmensbereichen und verschiedenen Branchen zeigen sich gewisse Unterschiede in der Nutzungsphase. Die Befragten stehen aktuell vor der Nutzung von vor allem teilautonomen KI-Systemen, die ausführende und analytische menschliche Tätigkeitenbeispielsweise durch Informationsbereitstellungen unterstützen. Wesentliche Ziele der KI-Nutzung sind die Effizienzsteigerung, Qualitätsverbesserung, Entscheidungsoptimierung sowie Unterstützung der Arbeitnehmer*innen. Allerdings werden in allen Unternehmen die fehlende Expertise sowie insgesamt die Komplexität des Themenfelds als Hinderungsgründe identifiziert. In allen Unternehmen und allen Unternehmensbereichen werden hohe Auswirkungen durch KI erwartet. Auf die Arbeitsgestaltung werden insgesamt eher positive Auswirkungen erwartet. Die Befragten schätzen die Bedeutung von KI, ihre Aufgeschlossenheit sowie ihr Vertrauen gegenüber KI als insgesamt hoch ein, ihr Verständnis von KI dagegen eher als gering. Tendenziell zeigt sich eine große Diskrepanz zwischen Selbst- und Fremdbild mit einer teils deutlich negativeren Wahrnehmung anderer. Die Befragten erwarten außerdem steigende Kompetenzanforderungen sowie einen hohen Weiterbildungsbedarf, insbesondere bezüglich des grundlegenden Verständnisses über KI. In den wenigsten Unternehmen existiert jedoch ein gezieltes Weiterbildungsangebot. Die Erkenntnisse aus der Befragung fließen im Rahmen des Kompetenzzentrums Arbeitswelt.Plus in die gezielte Gestaltung und Einführung KI-gestützter Arbeitsformen sowie bedarfsgerechter Unterstützungsangebote ein. Die hohe Komplexität der KI-Einführung sowie die sowohl technischen als auch mitarbeiterbezogenen Herausforderungen verdeutlichen den Bedarf für eine soziotechnische Perspektive und ein systematisches Vorgehen bei der Gestaltung dieses vielschichtigen Themenfelds.

Care robots in society: Knowledge and orientation needs - Pekkarinen, Satu; Hennala, Lea; Tuisku, Outi; Gustafsson, Christine; Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Melkas, Helinä (Gerontechnology)

The need for care robot orientation in elder care services - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helinä; Gustafsson, Christine (Gerontechnology)

Age and tenure diversity on the work floor: Evidence from a natural field experiment in production - Thommes, Kirsten; Klabuhn, Janny (Evidence-based HRM)

Care Robot Orientation: What, Who and How? Potential Users` Perceptions - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helina; Gustafsson, Christine (International Journal of Social Robotics)

Can digital feedback increase employee performance and energy efficiency in firms? Evidence from a field experiment - Hoffmann, Christin; Thommes, Kirsten (Journal of Economic Behavior & Organization)

Decisions on Extending Group Membership—Evidence from a Public Good Experiment - Grund, Christian; Harbring, Christine; Thommes, Kirsten; Tilkes, Katja Rebecca (Games)
We experimentally compare the consequences for group cooperation of two decision mechanisms involving the extension of group membership. We analyze an exogenous decision (random draw) and an endogenous decision (made by a particular group member) mechanism to extend a temporary agent’s group membership. Our results reveal that the prospect of group membership extension affects not only the temporary but also the permanent group members’ contributions with an endogenous mechanism.

Group (Re-) formation in public good games: The tale of the bad apple? - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Journal of Economic Behavior & Organization)

The Role of Contract Types for Employees’ Public Service Motivation - Grund, Christian; Thommes, Kirsten (Schmalenbach Business Review)

Peer influence on protest participation: Communication and trust between co-workers as inhibitors or facilitators of mobilization - Born, Marieke; Akkerman, Agnes; Thommes, Kirsten (Social science research)

Public good provision in blended groups of partners and strangers - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Economics Letters)

Behavioral spillovers from freeriding in multilevel interactions - Thommes, Kirsten; Vyrastekova, Jana; Akkerman, Agnes (Journal of Behavioral and Experimental Economics)

The internal market and the consumer: what consumers actually choose - Thommes, Kirsten; Faure, Michael; Heine, Klaus (Colum. J. Eur. L.)

The dark side of solidarity: social norms and social relations in the aftermath of strikes - Thommes, Kirsten; Akkerman, Agnes; Torenvlied, René; Born, Marieke (Industrial relations journal)

HRM and the use of personnel services: an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Weiland, Katrin; Thommes, Kirsten (International journal of manpower)

HR outsourcing and service quality: theoretical framework and empirical evidence - Braun, Irene; Pull, Kerstin; Alewell, Dorothea; Störmer, Susi; Thommes, Kirsten (Personnel Review)

Explanatory factors for firms’ use of temporary agency work in Germany - Thommes, Kirsten; Weiland, Katrin (European Management Journal)

Triggers of HR outsourcing decisions--an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Thommes, Kirsten; Weiland, Katrin (The International Journal of Human Resource Management)

Wer nutzt HR-Outsourcing? Zentrale Strukturvariablen und ihr Einfluss auf die Nachfrage nach Personaldienstleistungen - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (German Journal of Human Resource Management)

Methodologische Grundlagen und Besonderheiten der qualitativen Befragung von Experten in Unternehmen: Ein Leitfaden - Bähring, Katrin; Hauff, Sven; Sossdorf, Maik; Thommes, Kirsten (Die Unternehmung schweizerische Zeitschrift für Betriebswirtschaft)

Incentives to invest in the human capital of temporary agency workers - Schmidt, Stephanie; Thommes, Kirsten (German Journal of Human Resource Management)

Die Wirkungen des Outsourcings von Personalfunktionen - ein Überblick über Aussagen verschiedener theoretischer Ansätze - Alewell, Dorothea; Bähring, Katrin; Thommes, Kirsten (Jena: Sonderforschungsbereich)

Outsourcing HR functions. Development of an explanatory approach to firms'(non-existent) demand for personnel services - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (Management Revue)

Institutional structures of the flexible assignment of personnel between enterprises. An economic comparison of temporary agency work, interim management and consulting - Alewell, Dorothea; Bähring, Katrin; Thommes, Kirsten (Management Revue)

Clean up your network: how a strike changed the social networks of a working team - Thommes, Kirsten; Akkerman, Agnes (Team Performance Management: An International Journal)

History as a source of organizational identity creation - Oertel, Simon; Thommes, Kirsten (Organization Studies)
We analysed the self-representation of twelve watchmaking firms located in a cluster in East Germany to understand how they apply rhetorical history to craft their identity. The findings show that there are common elements of rhetorical history that help organizations craft their identity, but there are also differences based on each firm’s historical background. While some firms specifically relate their identity to their own history, others mainly employ cluster-level history, while still others may even self-construct fictional historical roots. By discussing these findings, we contribute to a better understanding of how an organization’s identity is crafted and how history is utilized in such identity creation.

Outsourcing von Personalfunktionen - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (Motive und Erfahrungen im Spiegel von Experteninterviews)

Shadows of the past: The effect of communist heritage on employee consultation - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (ILR Review)

Organizational Failure in the Aftermath of Institutional Upheaval - Thommes, Kirsten; Oertel, Simon; Walgenbach, Peter (Organization Studies)

History as a Source of Competitive Advantages - Thommes, Kirsten; Oertel, Simon (Scandinavian Management Journal)

Trust development in care robots by opinion leader in the society - Thommes, Kirsten; Johansson-Pajala, Rose-Marie; Gustaffson, Christine; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Melkas, Helinä; Hoppe, Julia Amelie (Gerontechnology)

The fast and the furious—An experimental investigation of the pace of life and risky speed choice in traffic - Goldbach, Carina; Hoffmann, Christin; Hoppe, Julia Amelie; Pitz, Thomas; Thommes, Kirsten (PloS ONE)

Using loss aversion to incentivize energy efficiency in a principal agent context - Evidence from a field experiment - Hoffmann, Christin; Thommes, Kirsten (Economics Letters)

Combining Egalitarian and Proportional Sharing rules in Team Tournaments to Incentivize Energy-Efficient Behavior in a Principal-Agent Context - Hoffmann, Christin; Thommes, Kirsten (Organization & Environment)

Embedding care robots into society and practice: Socio-technical considerations - Pekkarinen, Satu; Hennala, Lea; Tuisku, Outi; Gustafsson, Christine; Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Melkas, Helina (Futures)

Incongruent Patterns of Organizational Identity Crafting by Different Organizational Actors - Hein-Pensel, Franziska; Knorr, Karin; Oertel, Simon; Thommes, Kirsten (Academy of Management Proceedings)

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Speaking of Performance: Evaluating Team Members’ Performance with Open-Ended Audio Comments - Gutt, Jana Kim; Thommes, Kirsten (Academy of Management Proceedings)
Keywords: Microbiology

Seizing the Opportunity for Automation—How Traffic Density Determines Truck Drivers' Use of Cruise Control - Hoffmann, Christin; Thommes, Kirsten (IEEE Transactions on Human-Machine Systems)
Keywords: Artificial Intelligence; Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Signal Processing; Control and Systems Engineering; Human Factors and Ergonomics

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Rhetoricians of the past: Rhetorical history and the crafting of organizational identity - Knorr, Karin; Hein-Pensel, Franziska; Oertel, Simon; Thommes, Kirsten (Academy of Management Proceedings)

Long‐term effects of institutional conditions on perceived corruption – A study on organizational imprinting in post‐communist countries - Auer, Thorsten Fabian; Knorr, Karin; Thommes, Kirsten (Business Ethics, the Environment & Responsibility)
In this paper, we apply imprinting theory to examine how institutional transformation substantially influences perceptions of corruption that we argue to be incorporated to a varying extent in organizations founded in that period. For this purpose, we compare the effect of a sudden shock (dissolution of the Soviet Union) on the managers' present perceptions to that of a steady transition (EU accession). We consult the 5th round of the Business Environment and Enterprise Performance Survey from 2012 to 2014 analyzing 4715 interviews with managers of organizations from twelve Central and Eastern European countries. Our results reveal striking differences in the present perception of corruption for organizations founded immediately before and immediately after these institutional transitions. The study's results contribute to the research on imprinting theory regarding the relationship between organizations and institutional conditions that constitutes a lasting effect on organizational structures. Thus, applying an institutional perspective that considers less stable periods for organizations yields a promising avenue in research on organizational behavior.
Keywords: Central and Eastern Europe; corruption; imprinting theory; institutional transformation; shock-imprinting

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Die Wirkungen des Outsourcings von Personalfunktionen – ein Überblick über verschiedene theoretische Ansätze und Entwicklung eines umfassenden Wirkungssets/ Effects of the outsourcing of personnel functions – an overview of several theoretical approaches and development of a comprehensive set of effects - Alewell, Dorothea; Bähring, Katrin; Thommes, Kirsten (Arbeit)
Abstract Unternehmen, die über das Outsourcing von Personalfunktionen entscheiden, stehen vor einer komplexen Fragestellung, da mit dem Bezug extern erbrachter Personaldienstleistungen sehr unterschiedliche Wirkungen ausgelöst werden können. Diverse Theorieansätze machen Aussagen zu einzelnen Wirkungskategorien des Outsourcings. Jedoch gibt bisher kein Ansatz dem Entscheidungsträger in der Praxis eine umfassende Entscheidungshilfe. Hier setzt der vorliegende Artikel an: Aus Ansätzen zur zwischenbetrieblichen Arbeitsteilung wird ein umfassendes „Wirkungsset“ des Outsourcings von Personalfunktionen hergeleitet, welches sich als Checkliste relevanter Wirkungskategorien eignet und die Einseitigkeiten bisheriger Ansätze vermeidet.
Keywords: Industrial and Manufacturing Engineering

Aggregating Human Domain Knowledge for Feature Ranking - Kornowicz, Jaroslaw; Thommes, Kirsten (Artificial Intelligence in HCI)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Humans in XAI: Increased Reliance in Decision-Making Under Uncertainty by Using Explanation Strategies - Lammert, Olesja; Richter, Birte; Schütze, Christian; Thommes, Kirsten; Wrede, Britta (Frontiers in Behavioral Economics)

Time perspectives and collaborative performance in creative tasks - Auer, Thorsten Fabian; Hoppe, Julia Amelie; Thommes, Kirsten (Journal of Organizational Effectiveness: People and Performance)
Purpose The relationship between variation in time perspectives and collaborative performance is scarcely explored, and even less is known about the respective mechanisms that lead to varying task performance. Thus, we aim to further the literature on time perspectives and collaborative performance, shedding light on the underlying behavioral patterns. Design/methodology/approach We report a quasi-experiment analyzing the impact of past, present and future orientation variation in dyads ( N = 76) on their quantitative and qualitative performance when confronted with a simple incentivized creative task with constraints. Subsequently, we offer a qualitative analysis of comments given by the participants after the task on the collaboration. Findings Results indicate that a dyad's elevation of past orientation and diversity in future orientation negatively affect collaborative performance. At the same time, there is a positive effect of elevation of future orientation. The positive effect is driven by clear communication and agreement during the task, while the negative effect arises from work sharing and complementation. Practical implications This study provides insights for organizations on composing individuals regarding their temporal focus for collaborative tasks that should be executed rapidly and require creative solutions. Originality/value Our study distinguishes by considering the composition of past, present and future time perspectives in dyads and focuses on a creative task setting. Moreover, we explore the mechanisms in the dyads with a substantial elevation of/diversity in future orientation, leading to their stronger/weaker performance.
Keywords: Organizational Behavior and Human Resource Management

Can leaders motivate employees’ energy-efficient behavior with thoughtful communication? - Hoffmann, Christin; Thommes, Kirsten (Journal of Environmental Economics and Management)
Keywords: Management; Monitoring; Policy and Law; Economics and Econometrics

Emotional Debiasing Explanations for Decisions in HCI - Schütze, Christian; Lammert, Olesja; Richter, Birte; Thommes, Kirsten; Wrede, Britta (Artificial Intelligence in HCI)

Born in the GDR: Imprinting, Structural Inertia and the Survival Chances of Organizations - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (Academy of Management Annual Meeting Proceedings)

Age diversity and its effects on team performance - Klabuhn, Janny; Thommes, Kirsten (Academy of Management Proceedings)

Elements of Organizational Identity and the Role of a Firm’s History - Thommes, Kirsten; Oertel, Simon (Academy of Management Proceedings)

Entrepreneurial activity-The impact of childhood - Thommes, Kirsten (Academy of Management Proceedings)

The after effects of strikes on team collaboration-experimental evidence - Thommes, Kirsten; Akkerman, Agnes; Vyrastekova, Jana (Academy of Management Proceedings)

Improved Knowledge Changes the Mindset: Older Adults’ Perceptions of Care Robots - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helinä; Gustafsson, Christine (HCII 2019)
This paper explores Finnish, German and Swedish older adults’ perceptions of a future welfare service with increased use of welfare technologies, specifically care robots. The issues are the rapid digitalization and development of health and welfare technology, which presently is mainly technology driven (not need or user driven), and the demographic challenge. The aim of the study was to explore older adults’ perception of the future use of welfare technology or care robots. A qualitative approach with focus group discussions was employed, followed by thematic analysis. The results are presented in four overall themes: the impact on daily life for older adults and professional caregivers, codes of practice and terms of use, dissemination of information and knowledge, and conditions for successful implementation. There were significant differences in the informants’ attitudes toward and knowledge about care robots. However, the informants’ attitudes appeared to change during the focus groups and in general, became more positive. Authentic needs, which care robots could support, refer to independence, safety and security, and the ability to manage or ease daily life or working life. The results suggest that older adults, after receiving relevant information, were open to the idea of being supported by care robots in their daily lives.
Keywords: Care robots; Older adults; Implementation; Information; Perceptions; Welfare technology

Is Corruption Imprinted? A Study on Preconditions of Corruption in Post-Communist Countries - Knorr, Karin; Auer, Thorsten Fabian; Thommes, Kirsten (Academy of Management Proceedings)

Are Numbers or Words the Key to User Reliance on AI? - Papenkordt, Jörg; Ngonga-Ngomo, Axel-Cyrille; Thommes, Kirsten (Academy of Management Proceedings)

Oh my Goodness: Investigating the Goodness of Performance Appraisal Formats Between and Within Teams - Gutt, Jana Kim; Mehic, Miro; Thommes, Kirsten (Academy of Management Proceedings)

Comparing Humans and Algorithms in Feature Ranking: A Case-Study in the Medical Domain - Hanselle, Jonas; Kornowicz, Jaroslaw; Heid, Stefan; Thommes, Kirsten; Hüllermeier, Eyke (Lernen, Wissen, Daten, Analysen (LWDA) Conference Proceedings)
The selection of useful, informative, and meaningful features is a key prerequisite for the successful application of machine learning in practice, especially in knowledge-intense domains like decision support. Here, the task of feature selection, or ranking features by importance, can, in principle, be solved automatically in a data-driven way but also supported by expert knowledge. Besides, one may of course, conceive a combined approach, in which a learning algorithm closely interacts with a human expert. In any case, finding an optimal approach requires a basic understanding of human capabilities in judging the importance of features compared to those of a learning algorithm. Hereto, we conducted a case study in the medical domain, comparing feature rankings based on human judgment to rankings automatically derived from data. The quality of a ranking is determined by the performance of a decision list processing features in the order specified by the ranking, more specifically by so-called probabilistic scoring systems.

Managementpraktiken in KMU - Thommes, Kirsten (Controlling für kleine und mittlere Unternehmen)

Assistive robots in care: Expectations and perceptions of older people - Hoppe, Julia Amelie; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Melkas, Helinä; Tusku, Outi; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten (Aging between Participation and Simulation - Ethical Dimensions of Socially Assistive Technologies in elderly care)

Kooperation und Konkurrenz in Personaldienstleistungsbeziehungen - Bähring, Katrin; Thommes, Kirsten (Kooperation und Konkurrenz)

Determinanten der Nachfrage nach Personaldienstleistungen durch Unternehmen - Überlegungen zur "strukturellen Stimmigkeit" der Personalarbeit - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Thommes, Kirsten (Strukturelle Stimmigkeit in der Betriebswirtschaftslehre)

Contagious conflict: spill-over effects of labor conflict between and within organizations - Akkerman, Agnes; Torenvlied, René; Lehr, Alex; Thommes, Kirsten (Social conflict within and between groups)

Losing What You Never Had - Akkerman, Agnes; Manevska, Katerina; Thommes, Kirsten; Sluiter, Roderick (Employment Relations as Networks)

Determinants of Trust in Smart Technologies - Papenkordt, Jörg; Thommes, Kirsten (Human-Technology Interaction)

Die Rechte von Arbeitnehmervertretern in Ost- und Westeuropa - Einheitseuropa oder Zweiklassengesellschaft? - Thommes, Kirsten; Walgenbach, Peter; Oertel, Simon